Investigation of age, period, and cohort effects to understand Scotland's excess mortality: use of Lexis diagrams and intrinsic estimator regression modelling. (November 2017) - Parkinson, Jane; Minton, Jonathan; Lewsey, James; Bouttell, Janet; McCartney, Gerry
Abstract: Background: Mortality rates are higher in Scotland than in England and Wales, even after accounting for deprivation. This excess mortality is partly due to higher mortality from suicide, alcohol-related deaths, and drug-related deaths. We investigated whether age, period, or cohort effects from exposure to adversity from the 1980s might explain the recent trends in these outcomes in Scotland. Methods: Data on registered alcohol-related deaths (36 635) and suicide (31 061) for 1974–2013, and drug-related deaths (15 427) for 1979–2013 were obtained from the National Records of Scotland. To identify and quantify relative age–period–cohort effects, data were analysed by sex and deprivation using line plots, shaded contour plots (Lexis diagrams commonly used in demography but limited in epidemiology and health sciences), and intrinsic estimator regression modelling. Findings: Cohort effects were identified for people born between 1960 and 1980 for both drug-related deaths and suicide. The 1960–80 birth cohort had roughly a 30% higher risk of suicide than other generations, and the increase in risk of drug-related deaths was at least twice as high. Both cohort effects were largely driven by male sex and people living in the most deprived areas, but the birth cohort most affected by suicide occurred slightly earlier than for drug-related deaths. The timing of the cohort at highest risk also differed by deprivation for both suicide and drug-related deaths, being earlier for men in the most deprived group. By contrast, an age–period effect for working-age adults, particularly in the most deprived areas, helped explain the trends in alcohol-related deaths; the risk of these deaths increased at least two times from 1990 to the mid-2000s. Interpretation: The results for drug-related deaths and suicide are consistent with the hypothesis that exposure to the changing socioeconomic and political contexts of the 1980s created a delayed negative health impact because the populations most affected were the same as those subsequently with higher risks of mortality. Limitations include definition of death outcomes, changes to coding, the use of year of registration, difficulties in disentangling age–period–cohort effects, and only having a partial view of each birth cohort. The use of several methods in triangulation added strength to the findings. Funding: None.